2021
DOI: 10.1111/nph.17259
|View full text |Cite
|
Sign up to set email alerts
|

Geographical‐based variations in white truffle Tuber magnatum aroma is explained by quantitative differences in key volatile compounds

Abstract: Summary The factors that vary the aroma of Tuber magnatum fruiting bodies are poorly understood. The study determined the headspace aroma composition, sensory aroma profiles, maturity and bacterial communities from T. magnatum originating from Italy, Croatia, Hungary, and Serbia, and tested if truffle aroma is dependent on provenance and if fruiting body volatiles are explained by maturity and/or bacterial communities. Headspace volatile profiles were determined using gas chromatography–mass spectrometry–olf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
3
29
1
Order By: Relevance
“…Consistent with previous studies (Barbieri et al, 2007;Amicucci et al, 2018;Splivallo et al, 2019; et Niimi et al, 2021), the bacterial communities retrieved in the investigated white truffles were made up almost exclusively of Proteobacteria, mainly belonging to the α-Proteobacteria class. Bacteroidetes and Firmicutes were, overall, poorly represented (Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with previous studies (Barbieri et al, 2007;Amicucci et al, 2018;Splivallo et al, 2019; et Niimi et al, 2021), the bacterial communities retrieved in the investigated white truffles were made up almost exclusively of Proteobacteria, mainly belonging to the α-Proteobacteria class. Bacteroidetes and Firmicutes were, overall, poorly represented (Fig.…”
Section: Resultssupporting
confidence: 91%
“…These findings corroborate, at least in part, the results obtained by Niimi et al (2021), who described unusual patterns by analysing the composition of the bacterial communities associated with T. magnatum ascocarps of different provenance. However, while Niimi et al (2021) reported Pedobacter as a non-dominant genus in T. magnatum, OTUs of the genus Pedobacter were dominant within some of the investigated white truffle microbiota, in line with the results described for T. aestivum by Splivallo et al (2019). They found that about 30% of the examined fruiting bodies were colonized by microbial communities mainly constituted by Pedobacter, Polaromonas, or Pseudomonas genera (Splivallo et al, 2019).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations